Unbalanced Aryl Hydrocarbon Receptor Expression in Peripheral and Lesional T Cell Subsets of Atopic Dermatitis - Hu YQ; Zhang JZ (Dove Medical Press, 2023)
Yu-Qing Hu, Jian-Zhong Zhang Department of Dermatology, Peking University People's Hospital, Beijing, 100044, People's Republic of ChinaCorrespondence: Jian-Zhong Zhang, Department of Dermatology, Peking University People's Hospital, No. 11 South Avenue, Xi Zhi Men Street, Xicheng District, Beijing, 100044, People's Republic of China, Tel +86-10-88325472, Email rmzjz@126.comBackground and Objective: The aryl hydrocarbon receptor (AhR) is a ligand-activated transcription factor, which is involved in the pathogenesis of a variety of skin diseases such as atopic dermatitis (AD). In this study, we aimed to study the AhR-expressing cells in T helper 17 (Th17), T helper 22 (Th22), regulatory T cells (Treg) and B cells in peripheral blood and in AD skin lesions.Methods: Twenty AD patients defined according to the Chinese criteria of atopic dermatitis and eighteen healthy subjects were included in our study. The AhR-expressing Th17, Th22, Treg and total B cells in peripheral blood were measured by flow cytometry. The AhR+ Th17 cells and AhR+ Th22 cells in AD skin lesions were measured by immunofluorescence. The mRNA of AhR, interleukin (IL)-22, IL-17A, IL-10, Foxp3, RORγT and TGF-β in peripheral blood mononuclear cells (PBMCs) was measured by real-time quantitative polymerase chain reaction.Results: The expression of AhR in peripheral CD4+ T cells, Th22 cells, Treg cells and total B cells was significantly increased in AD. AhR+IL-17A+ and AhR+IL-22+ lymphocytes were also increased in AD skin lesions. The mRNA levels of AhR, IL-22 and IL-17A in PBMCs in AD patients were significantly higher. AhR mRNA levels in PBMCs positively correlated with peripheral basophil count, peripheral eosinophil count and mRNA levels of IL-22.Conclusion: AhR was highly expressed in subpopulations of CD4+ T cells in peripheral blood and skin lesions of AD, suggesting that AhR might contribute to the pathogenesis of AD.Keywords: aryl hydrocarbon receptor, atopic dermatitis, CD4+ T cells, Th22 cells, Th17 cells, B cells